2002
DOI: 10.1074/jbc.m110312200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of the Loss of High Affinity Agonist Binding to γ-Aminobutyric Acid Type A Receptors

Abstract: We reported previously that tyrosine 62 of the ␤2 subunit of the ␥-aminobutyric acid, type A (GABA A ) receptor is an important determinant of high affinity agonist binding and that recombinant ␣1␤2␥2 L receptors carrying the Y62S mutation lack measurable high affinity sites for [ 3 H]muscimol. We have now examined the effects of disrupting these sites on the macroscopic desensitization properties of receptors expressed in Xenopus oocytes. Desensitization was measured by the ability of low concentrations of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…This creates a use dependence for P2X 3 inhibition (Fig. 6 B) similar to that seen in other channels (Bartrup and Newberry, 1996;Newell and Dunn, 2002).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This creates a use dependence for P2X 3 inhibition (Fig. 6 B) similar to that seen in other channels (Bartrup and Newberry, 1996;Newell and Dunn, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Nicotinic acetylcholine receptors (nAChR), GABA A receptors, 5-hydroxytryptamine receptors, and P2X 1 receptors are desensitized by concentrations of agonist that are lower than those required for channel activation (Katz and Theseleff, 1957;Bartrup and Newberry, 1996;Newell and Dunn, 2002;Paradiso and Steinbach, 2003). We found that 60 s of 0.5 nM ATP inhibited Ͼ50% of P2X 3 current after activation by high [agonist] (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such action may be expected if DCUK-OEt is shifting the GABA A receptor into a state more likely to be in an open channel configuration. The GABA A receptor has been shown to display two affinity states for agonists such as muscimol 46, 47 and the high affinity state of the GABA A receptor has been proposed to represent stabilization of the desensitized form of the receptor 48 . One can speculate that DCUK-OEt is increasing the proportion of receptors in a low affinity state at any particular concentration of agonist (muscimol).…”
Section: Discussionmentioning
confidence: 99%
“…1). Additional evidence suggested involvement of the corresponding residue in the process of desensitization (Newell and Dunn 2002).…”
mentioning
confidence: 99%